Integrasi keilmuan interdisipliner pada Kurikulum UIN Raden Fatah Palembang - Ahmad Zainuri; K.A. Bukhori (Al-Ulum, 2019)
This article designates the change of IAIN Raden Fatah Palembang into UIN substantial changes in the structure of scientific buildings (epistemology of science) therein. The construction the epistemology of science integration is then called “rumah ilmu” (the "house of science"). The concept of the paradigm is elaborated in four primary areas of a curriculum, namely the philosophical, material, methodological, and strategic domains. Concerning the current Industrial Revolution 4.0 era, the importance of the integrative-interconnected scientific paradigm at UIN Raden Fatah, which synergizes Islamic science and science-technology in the principle of monotheism, has contributed to the forming a unity of truth and unity of knowledge.